EDUKASI HUKUM DAN EKOLOGI PERAIRAN LAUT PADA KELOMPOK MASYARAKAT NELAYAN PESISIR BULUKUMBA - Hendrianto, Henrdianto; Tahirah, Tahirah (Program Studi Ilmu Kelautan, FMIPA Universitas Tanjungp, 2025)
Coastal communities play an important role in maintaining the sustainability of marine ecosystems, but low understanding of ecological and legal aspects often leads to excessive exploitation of marine resources. This educational activity aims to increase awareness of fishing communities regarding the sustainable use of marine resources and provide an understanding of the applicable legal regulations in coastal environmental management. The methods used include interactive socialization, training in environmentally friendly fishing practices, and legal counseling related to fisheries and marine conservation. Educational materials include the principles of sustainable fisheries, coastal waste management, and legal regulations such as the Fisheries Act, the Environmental Act, and policies regarding Illegal, Unreported, and Unregulated (IUU) Fishing. The results of this program showed an increase in participants' understanding, as measured by pre-tests and post-tests, where 15 out of 20 participants experienced an increase in awareness of the importance of maintaining marine ecosystems and understanding the legal consequences of irresponsible exploitation. The expected long-term impact is the formation of groups of environmentally conscious fishermen who act as agents of change in their communities. In addition, this legal education is also expected to increase community involvement in environmental monitoring efforts and collaboration with authorities to prevent illegal fishing practices. With an education-based approach and active community participation, the sustainability of marine resources can be maintained, supporting the welfare of fishermen, and ensuring that marine ecosystems remain productive for future generations.